Prediction Of Employee Disciplinary Punishment At The Departmen Of Agriculture Payakumbuh City Through Approach Binary Logistic Regression - Susi Suheni; Jerry Heikal (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2024)
The Payakumbuh City Agricultural Service is one of the regional apparatus organizations which plays a role in providing direct services to the farming community, which is responsible for increasing the production of agricultural products which are useful for food supply as well as in terms of improving the welfare of farmers. Implementing work discipline is an important element in maintaining organizational quality and efficiency. Work discipline is the main foundation in creating an effective and efficient organization. Discipline reflects an employee's commitment to his responsibilities, including meeting work standards set by the organization. In the work environment, violations of organizational rules and policies cannot be avoided. Therefore, giving disciplinary punishment is an important instrument for handling these violations while preventing similar violations from occurring in the future. This research aims to predict employees within the Payakumbuh City Agriculture Service using Binnary Logistic Regression, which will later determine which employees will given disciplinary punishment and which employees will not be given disciplinary punishment. Disciplinary punishment aims to provide a deterrent effect and improve employee behavior. The data used in this research were 96 employee data from the Payakumbuh City Agriculture Service. Where there are 7 (seven) independent variables and 1 (one) dependent variable and from the processing results there are 2 (two) significant variables, namely Late and Fast Repeat.